2017
DOI: 10.1159/000478681
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Pycnogenol Against Oxygen-Glucose Deprivation/Reoxygenation-Induced Injury in Primary Rat Astrocytes via NF-κB and ERK1/2 MAPK Pathways

Abstract: Backgrounds/Aims: Pycnogenol (PYC) is a patented mix of bioflavonoids with potent anti-oxidant and anti-inflammatory properties. In this study, we investigated the effects of PYC on oxygen-glucose deprivation/reoxygenation (OGD/R)-induced injury in primary rat astrocytes. Methods: The primary rat astrocytes were randomly divided into 6 groups, blank control, OGD/R, OGD/R+PYC (10, 20, 40, and 60 µg/mL). The cell activity were detected by MTT and LDH assays, then the levels of oxidant products [malondialdehyde (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…OGD can induce oxidative stress, inflammatory cytokine accumulation, and MMP dissipation via NF-κB and ERK1/2 pathways in primary rat astrocytes. HG can result in the over-production of ROS and a loss of MMP [41][42][43]. Indeed, the results of this study showed that gp91phox is the common denominator in both processes.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 56%
“…OGD can induce oxidative stress, inflammatory cytokine accumulation, and MMP dissipation via NF-κB and ERK1/2 pathways in primary rat astrocytes. HG can result in the over-production of ROS and a loss of MMP [41][42][43]. Indeed, the results of this study showed that gp91phox is the common denominator in both processes.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 56%
“…Cocultures were established using a 6-well Transwell cell culture system with a 0.4-μm membrane that cells cannot get through. For the SCI-AST+PDTC group, 5×10 4 astrocytes were seeded on the upper chamber and supplemented with 10 mM PDTC [27][28][29]. For the SCI-AST+MSC and SCI-AST+MSC+TNFα groups, 5×10 4 astrocytes were seeded on the upper chamber in the absence and presence of TNF-α (50 ng/mL; R&D Systems), respectively [30][31][32][33][34], with 5×10 4 MSCs seeded on the lower chamber.…”
Section: Astrocyte Coculture With Mscs or Msc-exomentioning
confidence: 99%
“…; Xia et al . ). As shown here, the immunoreactivity of GFAP protein was increased in brain after MCAO and in astrocytes after OGD, and it was markedly inhibited after Z‐GS treatment (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Sustained activation of pro-inflammatory cytokines as well as enhanced expression of GFAP, are known to aggravate brain damage (Hennessy et al 2015), while the inhibition of these cytokines and activated astrocytes is beneficial to the therapy of ischemic stroke (Ashafaq et al 2016;Pan et al 2017). It was also reported that OGD induced the secretion of pro-inflammatory cytokines and the activation of astrocytes in vitro (Li et al 2015b;Xia et al 2017). As shown here, the immunoreactivity of GFAP protein was increased in brain after MCAO and in astrocytes after OGD, and it was markedly inhibited after Z-GS treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%